1) 4y-26=8y+14
4у-8у=14+26
-4у=40
у=-10
2) 4×(4+5x)-5×(1-2x)=-1
16+20х-5+10х=-1
11+30х=-1
30х=-1-11
30х=-12
х=-2/5
х=-0,4
3) 3(4-3x)-2=-10(9x1)
12-9х-2=-10*9х
10-9х=-90х
-9х+90х=-10
81х=-10
х=-10/81
Пошаговое объяснение:
1)-1
2)-2,5
1) 4у-26=8у+14
у=-1
2)4×(4+5х)-5×(1-2х)=-1
16+20х-5+10х+1=0
Х=-2,5
3)3(4-3х)-2=-10(не понятно, какой знак между 9х и 1)
1) 4y-26=8y+14
4у-8у=14+26
-4у=40
у=-10
2) 4×(4+5x)-5×(1-2x)=-1
16+20х-5+10х=-1
11+30х=-1
30х=-1-11
30х=-12
х=-2/5
х=-0,4
3) 3(4-3x)-2=-10(9x1)
12-9х-2=-10*9х
10-9х=-90х
-9х+90х=-10
81х=-10
х=-10/81
Пошаговое объяснение:
1)-1
2)-2,5
Пошаговое объяснение:
1) 4у-26=8у+14
4у-8у=14+26
-4у=40
у=-1
2)4×(4+5х)-5×(1-2х)=-1
16+20х-5+10х+1=0
30х=-12
Х=-2,5
3)3(4-3х)-2=-10(не понятно, какой знак между 9х и 1)